Efeito da alimentação artificial no desenvolvimento de Melipona compressipes fasciculata (Hymenoptera, Apidae) na Baixada Ocidental Maranhense - Vasconcelos, Antônio Tomaz Correia de (2009)
This study aimed to evaluate the effect of different food supplements in newly populated colonies of Melipona fasciculata compressipes to determine the best foods for affected increase in the weight of the colonies and their productive development. In an experimental field located in the municipality of Palmerândia, Maranhense Western Lowland, during the months from november 2008 to march 2009 were installed in 25 colonies fed differential with 05 additional food, comprising 05 treatments and 05 repetitions. The foods were: honey, sugar and water, sugar, water and lemon, sugar, water, lemon, vitamin, essence, sugar, water, lemon, vitamin, essence and pollen. By end of 75 days was observed that the development of colonies is influenced by different types of affected food and the more that is added to affected food nutrients in colonies of its better adaptation after a settlement, therefore its development. However no significant difference between the means of each treatment during each period of monitoring. Thus the weight of colonies of Melipona fasciculata compresipes varies depending on the food provided, all dietary supplements showed no risk of toxicity and the colonies had higher weight when fed fortified supplements.